Students' Perception Towards The Use of ELSA Speak App for Speaking Practice - Alsuna Nabilah; Davina Azhaar; Annindya Putri Syarifatunnisa; Tahira Az-Zahra; Atik Yuliyani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The rapid advancement of technology in recent years has integrated into language learning. Therefore, this study investigates the students’ perception of the use of the ELSA App in speaking practice skills. A qualitative design was chosen for this research and the data were collected through a close-ended and open-ended questionnaire. This research used a random sampling of participants from the English Education Department in UIN Syarif Hidayatullah Jakarta who use the ELSA Speak App to improve their speaking skills. The result of this study showed a positive perception in the use of the ELSA Speak App that the ELSA App’s features are able to help students in speaking practice.